1997
DOI: 10.1084/jem.185.8.1511
|View full text |Cite
|
Sign up to set email alerts
|

Differential Induction of Apoptosis by Fas–Fas Ligand Interactions in Human Monocytes and Macrophages

Abstract: Human monocytes undergo spontaneous apoptosis upon culture in vitro; removal of serum from the media dramatically increases the rate of this process. Monocyte apoptosis can be significantly abrogated by the addition of growth factors or proinflammatory mediators. We have evaluated the role of the endogenous Fas–Fas ligand (FasL) interaction in the induction of this spontaneous apoptosis and found that a Fas–immunoglobulin (Ig) fusion protein, an antagonistic anti-Fas monoclonal antibody and a rabbit anti-FasL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
181
2
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(210 citation statements)
references
References 29 publications
24
181
2
3
Order By: Relevance
“…The Fas/FasL system is believed to play an important role in normal monocyte physiology (16). Monocytes are able to undergo apoptosis via an autocrine or paracrine mechanism that is dependent upon the expression of both Fas and FasL (40). This has been confirmed by in vitro studies which have shown that anti-Fas or anti-FasL neutralizing Abs can block monocyte spontaneous apoptosis during differentiation (40).…”
Section: Discussionsupporting
confidence: 52%
“…The Fas/FasL system is believed to play an important role in normal monocyte physiology (16). Monocytes are able to undergo apoptosis via an autocrine or paracrine mechanism that is dependent upon the expression of both Fas and FasL (40). This has been confirmed by in vitro studies which have shown that anti-Fas or anti-FasL neutralizing Abs can block monocyte spontaneous apoptosis during differentiation (40).…”
Section: Discussionsupporting
confidence: 52%
“…Peripheral blood monocytes were then isolated from the MNCs by countercurrent centrifugal elutriation (Beckman Coulter, Palo Alto, CA) (13,14). Monocytes were differentiated to macrophages in RPMI 1640 containing 20% heat-inactivated fetal bovine serum (FBS) and 1 g/ml polymyxin B sulfate (Sigma) (15,16). All experiments using human cells were approved by the Institutional Review Boards of Northwestern University and Saint Louis University.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Conversely, activation of monocytes by LPS or TNF-␣ promotes pro-inflammatory-induced monocyte survival. 16 The fact that we observed an increase in the frequency and absolute numbers of circulating monocytes in patients with PBC compared with sex-matched controls of similar age suggests that monocytes were activated in vivo as a result of chronic inflammation endured by the patients. As such, freshly isolated monocytes from patients, as opposed to normal controls, are more resistant to self-induced cellular death because of their activation status.…”
Section: Discussionmentioning
confidence: 99%